Buy Now Pay Later from an Islamic Perspective: Implications for Financial Management and Sustainability among Millennials - Harahap, Ainul Yusna; Putri, Desyana; Fajriah, Agustina Nurul; Ardiyanti, Dyah Ayu; Saputra, Ryanda (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
Buy Now Pay Later (BNPL) services have become increasingly popular among millennials in Langsa City. However, the widespread use of BNPL raises potential conflicts with Islamic financial principles such as riba, gharar and maysir. This study aims to analyze BNPL’s compliance with Islamic financial principles and its implications for the financial management and financial sustainability of millennials in Langsa City. The research employs a mixed methods approach by combining a questionnaire survey and interviews. A total of 150 millennial respondents were selected through cluster sampling and the data were analyzed using SmartPLS. The results indicate that BNPL has a positive and significant effect on millennials’ financial management and financial sustainability. However, BNPL still contains elements of riba and gharar. The analysis shows that Islamic financial principles mediate the influence of BNPL on financial management, but not on financial sustainability. Overall, BNPL has potential as a beneficial modern financial instrument if aligned with Sharia principles. Enhancing Islamic financial literacy is crucial to minimize Sharia-related and financial risks.